Ringan di Meja Hijau, Berat di Nurani: Pelanggaran Kode Etik Hakim dalam Korupsi 271 Triliun Harvey Moeis dan Runtuhnya Kepercayaan Publik - M, Mulyadi; Pradiani, Canisya; Sagita, Nabila; Al Hafizh, Muhammad Fadhlan; Alfarizi, Rizqie Achmad; Y. S, Jevon Verrell; Ginting, Yovani Yolanda Putri; Putra R, Daffa Charisma (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The corruption case involving Harvey Moeis, with state losses reaching 271 trillion rupiah, has brought sharp scrutiny to the integrity and professionalism of judges in Indonesia. The public's perception of a lenient verdict has triggered allegations of violations of the judicial code of ethics, potentially undermining public trust in the judiciary. This study aims to analyze in depth the alleged violations of the judicial code of ethics in this case, as well as its impact on public trust. The research method used is a case study with a qualitative approach, through the analysis of documents, news, and literature studies. The results of the study indicate indications of violations of the judicial code of ethics, reflected in the significant disparity between the prosecutor's demands and the judge's verdict. The implications of this case are extensive, not only damaging the image of the judiciary, but also threatening the rule of law and justice in Indonesia.